Assessment of farmer and non-farmer health effects related to organophosphate pesticides exposure using blood cholinesterase activity as a biomarker in agricultural area at Ongkharak District Nakhon Nayok Province Thailand - Wachiraporn Wilaiwan (Chulalongkorn University, 2014)
Thesis (M.P.H.)--Chulalongkorn University, 2012